DAUR ULANG LIMBAH KEMASAN MULTILAYER SEBAGAI BAHAN PEMBUATAN TAWAS UNTUK MENURUNKAN PARAMETER PENCEMAR INDUSTRI TAHU - Novi Eka Mayangsari; Tarikh Azis Ramadani; Nella Maulidiyatul Jannah; Dika Rahayu Widiana (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
An increase in population will have a major impact on the environment, such as an increase in the volume of waste. The second largest composition of waste after food waste is plastic waste, which is a type of waste that is difficult to decompose. One of them is coffee packaging plastic waste. Recycling is a way that can be done to reduce coffee packaging plastic waste, namely by separating the plastic layer and the aluminum layer. The aluminum layer can be processed into alum. The purpose of this study is to separate the plastic layer and aluminum layer using the green solvent method using methanoic acid, the effect of variations in the concentration of KOH with a concentration of H2SO4 6M, and determining the optimum dose in reducing COD and BOD levels in wastewater tofu industry. The results showed that with the variation of the higher concentration of KOH, the yield of alum produced was also higher. Alum research results were compared with commercial alum. Comparison of these two types of alum shows that alum produced in this study resulted in higher COD and BOD removal efficiency than commercial alum, but with different coagulant doses.